2022
DOI: 10.3389/fmicb.2022.820509
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Rumen Bacterial Community Induced by the Dietary Physically Effective Neutral Detergent Fiber Levels in Goat Diets

Abstract: Physically effective neutral detergent fiber (peNDF) is a concept that accounts for the particle length of NDF in a feed, sustaining the normal chewing behavior and rumen fermentation of ruminants. This study aimed to elucidate the effects of dietary peNDF on growth performance and bacterial communities in the rumen of goats through a high-throughput sequencing technique. A total of 30 male Lezhi black goats were randomly assigned to five groups, corresponding to five diets with identical compositions and nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
3
10
0
Order By: Relevance
“…Bacteroidetes and Firmicutes were the dominant bacteria phyla, as was reported in cattle ( Xin et al, 2019 ), dairy cows ( Wang et al, 2019b ), goats ( Xue et al, 2022 ), and sheep ( Castro-Carrera et al, 2014 ). These findings suggest that these two phyla play important roles in feed digestion and metabolism in the rumen.…”
Section: Discussionsupporting
confidence: 60%
“…Bacteroidetes and Firmicutes were the dominant bacteria phyla, as was reported in cattle ( Xin et al, 2019 ), dairy cows ( Wang et al, 2019b ), goats ( Xue et al, 2022 ), and sheep ( Castro-Carrera et al, 2014 ). These findings suggest that these two phyla play important roles in feed digestion and metabolism in the rumen.…”
Section: Discussionsupporting
confidence: 60%
“…A recent meta-analysis demonstrated a strong positive correlation between daily CH 4 production and DMI in finishing beef cattle (Smith et al, 2021). Hence, we found that the variation trend of daily CH 4 production was consistent with the DMI when goats were fed diets with different levels of peNDF (Xue et al, 2022), while the daily CH 4 production per kg DMI was not affected by the dietary peNDF content.…”
Section: E Ects Of Dietary Pendf On Characteristics Of Ruminal Fermen...supporting
confidence: 70%
“…Excessively small or fine particle size would result in a decrease in rumen pH, negatively affecting fiber digestion, feed intake, and feed efficiency (Tafaj et al, 2005 ). In our recently published study, the feed intake of goats increased first and then decreased with the decrease of dietary peNDF >1.18 content from 33.0 to 24.8% (678 vs. 704 vs. 737 vs. 831 vs. 702 g/day), and reached the maximum at the content of peNDF >1.18 was 26.5% (Xue et al, 2022 ). The same trend appeared in the apparent digestibility of nutrients in this study, with the highest and the lowest digestibility of DM, OM, CP, NDF, and ADF observed in the 28.14% and 24.75% peNDF >1.18 treatment.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, the enrichment of Prevotella_1 in TAL might attenuate the adverse impacts of TA on the protein fermentation in rumen, and this inference is consistent with the unaffected NH 3 -N concentration in TAL compared to CON. Moreover, the negative correlation between the ruminal Prevotella_1 abundance and amino acid metabolism and energy metabolism in goats was demonstrated by a recent study (61). This finding implies that a potential relationship might exist between the enrichment of Prevotella_1 and the reduction of GLB, IgG, GH, and IGF-1 in TAL goats, which requires further explorations to be verified.…”
Section: Discussionmentioning
confidence: 82%